Literature Review: Korelasi Neutrophil Lymphocyte Ratio dan Platelet Lymphocyte Ratio terhadap Kejadian Kaki Diabetes - Syifa Khairani; Fauzia Noor Liani; Dewi Indah Noviana Pratiwi; Mohammad Rudiansyah; Azma Rosida (Homeostasis, 2022)
Abstract: One of the complications of diabetes is diabetic foot ulcers. In diabetic foot, immune changes result in reduced healing response in diabetic ulcers. There is a method for assessing inflammatory stress, namely the Neutrophil Lymphocyte Ratio (NLR), which indicates the patient's response to inflammatory disorders, accompanied by an increase in neutrophils which is a response to stress. Platelet Lymphocyte Ratio (PLR) is an inflammatory marker that can be used in many diseases to predict inflammation that is affected by several inflammatory conditions. High PLR reflects inflammation, atherosclerosis and platelet activation. This literature review has the aim of collecting data and analyzing the relationship between Neutrophil Lymphocyte Ratio and Platelet Lymphocyte Ratio on the incidence of diabetic foot and understanding the mechanism underlying changes in the levels of Neutrophil Lymphocyte Ratio and Platelet Lymphocyte Ratio which can cause complications of diabetic foot. The literature articles used are 10 articles obtained from databases of medical journals, in the form of Pubmed and Google Scholar. The author takes English and Indonesian journals with a time span of 2009-2020. The results obtained in this literature review are that there is an increase in PLR and NLR values with the severity of diabetic foot ulcers. Further research is needed to determine the correlation between Neutrophil Lymphocyte Ratio and Platelet Lymphocyte Ratio on the incidence of diabetic foot. Keywords: diabetic foot ulcer, neutrophil lymphocyte ratio, platelet lymphocyte ratio Abstrak: Salah satu komplikasi dari diabetes ialah ulkus kaki diabetes. Pada kaki diabetes sendiri perubahan imun mengakibatkan respons penyembuhan pada ulkus diabetikum berkurang. Terdapat metode untuk menilai stress peradangan yaitu Neutrophil Lymphocyte Ratio (NLR), yang menandakan respons pasien atas gangguan inflamasi, disertai gambaran peningkatan neutrofil yang merupakan respons terhadap stress. Platelet Lymphocyte Ratio (PLR) adalah penanda inflamasi yang dapat digunakan dalam banyak penyakit untuk memprediksi peradangan yang dipengaruhi oleh beberapa kondisi inflamasi. PLR yang tinggi mencerminkan peradangan, aterosklerosis dan aktivasi platelet. Literature review ini memiliki tujuan berupa mengumpulkan data serta menganalisis hubungan Neutrophyl Lymphocyte Ratio dan Platelet Lymphocyte Ratio terhadap kejadian kaki diabetes serta memahami mekanisme yang mendasari perubahan kadar Neutrophyl Lymphocyte Ratio dan Platelet Lymphocyte Ratio yang mana dapat membuat komplikasi kaki diabetes. Artikel literatur yang digunakan ialah 10 artikel yang didapat dari basis data jurnal kedokteran, berupa Pubmed dan Google Scholar. Penulis mengambil jurnal Bahasa inggris dan Bahasa Indonesia dengan rentang waktu 2009-2020. Hasil yang diperoleh pada literature review ini ialah terdapat peningkatan nilai PLR dan NLR dengan seiringnya keparahan ulkus kaki diabetes. Penelitian lebih lanjut diperlukan untuk mengetahui korelasi antara Neutrophil Lymphocyte Ratio dan Platelet Lymphocyte Ratio terhadap kejadian kaki diabetes. Kata-kata kunci: kaki diabetes, rasio neutrofil limfosit, rasio platelet limfosit